Effects of incorporating nanosized calcium phosphate particles on properties of whisker-reinforced dental composites - Xu, Hockin H. K.; Sun, Limin; Weir, Mike D.; Takagi, Shozo; Chow, Laurence C.; Hockey, Bernard (Journal of biomedical materials research. Part B, Applied biomaterials, 2007)
Clinical data indicate that secondary caries and restoration fracture are the most common problems facing tooth restorations. Our ultimate goal was to develop mechanically‐strong and caries‐inhibiting dental composites. The specific goal of this pilot study was to understand the relationships between composite properties and the ratio of reinforcement filler/releasing filler. Nanoparticles of monocalcium phosphate monohydrate (MCPM) were synthesized and incorporated into a dental resin for the first time. Silicon carbide whiskers were fused with silica nanoparticles and mixed with the MCPM particles at MCPM/whisker mass ratios of 1:0, 2:1, 1:1, 1:2, and 0:1. The composites were immersed for 1–56 days to measure Ca and PO4 release. When the MCPM/whisker ratio was changed from 0:1 to 1:2, the composite flexural strength (mean ± SD; n = 5) decreased from 174 ± 26 MPa to 138 ± 9 MPa (p < 0.05). A commercial nonreleasing composite had a strength of 112 ± 14 MPa. When the MCPM/whisker ratio was changed from 1:2 to 1:1, the Ca concentration at 56 days increased from 0.77 ± 0.04 mmol/L to 1.74 ± 0.06 mmol/L (p < 0.05). The corresponding PO4 concentration increased from 3.88 ± 0.21 mmol/L to 9.95 ± 0.69 mmol/L (p < 0.05). Relationships were established between the amount of release and the MCPM volume fraction vMCPM in the resin: [Ca]= 42.9 v MCPM2.7, and [PO4] = 48.7 v MCPM1.4. In summary, the method of combining nanosized releasing fillers with reinforcing fillers yielded Ca‐ and PO4‐releasing composites with mechanical properties matching or exceeding a commercial stress‐bearing, nonreleasing composite. This method may be applicable to the use of other Ca–PO4 fillers in developing composites with high stress‐bearing and caries‐preventing capabilities, a combination not yet available in any dental materials. © 2006 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2006